Modeling of fragment formation of parchment coffee beans for rapid heat and mass transfer during fluidization drying - Chaiwat Rattanamechaiskul; Nittaya Junka (My University, 2020)
Fluidization drying technique allows fluidized coffee beans to float, resulting in rapid heat and mass transfer, which have been directly associated with an increase in the moisture gradient, creating bean stress. Bean quality is determined by the degree of bean fragmentation caused by drying, an important standard considered in purchasing and selling. We have modeled the drying process to explain the kinetics of bean fragmentation. Drying temperature affected the drying rate and fragmentation of parchment coffee beans. Specific energy consumption varied with the drying rate. Comparing the experimental results for the predicted average moisture content and the predicted bean fragment formation, using a first-order equation, yielded satisfactory results. Modeling enabled the prediction of drying conditions with the lowest possible specific energy consumption, while the final moisture content and bean fragment percentage met commercial standards. Practical applications The advantage of fluidization drying is rapid heat and mass transfer between material and hot air. In spite of this advantage, a rapid reduction of moisture during fluidization may cause stress to the material, resulting in bean fragmentation. Fragmentation is a physical measurement of bean quality after undergoing the drying process; it is one of the standards that is taken into consideration by buyers and sellers. We have developed a model to explain and predict the kinetics of bean fragmentation during the complex drying process. The predictions of our model can be used as guidelines for drying parchment coffee beans by the fluidization technique.
Keywords: Fluidization; Fragmentation; Coffee bean; Coffee research and impacts